Application of Bacterial Biofilm in Remediation of Crude Oil Polluted Mangroove Forest Water - Abdulganiyu Mohammed Galadima; Reuben Nwoye Okechi; Angela Chika Udebuani; Ibrahim Abubakar; Said Sani Said (BIORE Scientia Publisher, 2026)
Oil and gas industrial activities have caused serious water pollution and adverse health effects on human, animals, plants, and aquatic organisms. Biofilms have significant potential for remediation of polluted water. This study aimed at evaluating the efficiency of bacterial biofilm in bioremediation of crude oil polluted mangrove forest water of Gbaramatu Kingdom of Warri South-West, Delta state, Nigeria. The total petroleum hydrocarbon (TPH) was determined by gravimetric while total hydrocarbon content (THC) and total oil and grease (TOG) were estimated using Fourier Transform Infrared (FTIR) spectroscopic technique. The screening of bacterial isolates for biofilm formation was conducted using microtitre plate assay and tube method. The crude oil degradation capacities of the bacterial isolates and bacterial biofilms were determined by gravimetric technique and GC-MS analysis. The mangrove water contains significant (p < 0.05) amount of THC (823.05 mg/L), TPH (1132.11 mg/L), and TOG (333.99 mg/L). The result showed that Pseudomonas isolates exhibited high significant (p < 0.05) growth intensity (80.94 %) compared to the Bacillus (75.04 %) and Micrococcus (53.20 %) isolates. The Pseudomonas (1.070 OD) and Micrococcus (0.818 OD) produced maximum significant (p < 0.05) amount of biofilm compared to the Bacillus (0.082 OD). The bacterial biofilms displayed more significant (p < 0.05) crude oil degradation efficiency compared to the mixed bacterial isolates. More number of peaks, each represents different petroleum components were observed in the untreated water sample. The water sample treated with the bacterial biofilm showed disappearance of these peaks with few peaks of low intensity. Total degradation of short-chain hydrocarbons and low molecular weight PAHs coupled with partial degradation of long-chain hydrocarbons and high molecular weight PAHs by the biofilm was observed. The bacterial biofilms are highly effective in degradation of crude oil components than the bacterial isolates indicating that the biofilms are significant agents for bioremediation of crude oil polluted environment.